If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+-5x=-3x
We move all terms to the left:
x+-5x-(-3x)=0
We add all the numbers together, and all the variables
-4x-(-3x)=0
We get rid of parentheses
-4x+3x=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0
| x+-4x=-3x | | 3x+12=10x-8 | | 3x÷9=20 | | -5x+3=133x-9=-15 | | 2a^2=1764 | | 6(3x-2)=-25 | | |2x+1|=x+5 | | 3x+9=7x+8 | | y=7y-12 | | 4(x-9=-16 | | 14p-6(9+3)=p+9 | | 17p-6(9+3)=p+9 | | 10x+135=5 | | m2+7=88 | | t/4=39/52 | | 3x-8xx=40 | | 6x+2(-2x-1,5)=18 | | 2x-18+18=86+18 | | 0.6^x=3 | | 6x-4=85 | | (x)÷4=105 | | x÷4=105 | | 5/3=6/n+2 | | w2+4w+3=0 | | 880-x=35.5 | | 9e=7e+10 | | 80-x=355.5 | | x/5+10=33 | | -2.9a+3.7=16.1+3.1a | | 6/14=7/n-3 | | 2x2+2x=80 | | Y=5x^2-10+14 |